2020
DOI: 10.3390/app10134680
|View full text |Cite
|
Sign up to set email alerts
|

Research and Implementation of Axial 3D Printing Method for PLA Pipes

Abstract: Additive manufacturing has been applied in many fields, but its layer-by-layer fabrication process leads to a weak inter-layer bond strength of printed parts, so it cannot meet the higher requirements for mechanical properties of the industry. At present, many researchers are studying the printing path planning method to improve the mechanical properties of printed parts. This paper proposes a method to plan the printing path according to the actual stress of pipe parts, and introduces the realization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Rotary 3D printing has been applied with a bioink blend for tissue-engineered small-diameter vascular constructs in AM technologies (Freeman et al, 2019), which validates the feasibility of rotary 3D printing. Similarly, the axial 3D printing method is researched and implemented for standard polylactic acid (PLA) pipes based on a five-axis material extrusion platform (Zhang et al, 2020). This research proves that axial printing enhances pipe parts' mechanical properties based on tensile and bending experiments.…”
Section: Development Of Surface Formationmentioning
confidence: 70%
See 1 more Smart Citation
“…Rotary 3D printing has been applied with a bioink blend for tissue-engineered small-diameter vascular constructs in AM technologies (Freeman et al, 2019), which validates the feasibility of rotary 3D printing. Similarly, the axial 3D printing method is researched and implemented for standard polylactic acid (PLA) pipes based on a five-axis material extrusion platform (Zhang et al, 2020). This research proves that axial printing enhances pipe parts' mechanical properties based on tensile and bending experiments.…”
Section: Development Of Surface Formationmentioning
confidence: 70%
“…Theoretically, there are no constraints of the CAD model for printing process simulation based on G-code with the aid of Cura. However, to avoid interference between the printing head and the build platform or the printed part during printing in the simulation, the angle between the generation line and the build platform’s plane should be limited to [60°, 135°] (Zhao, 2021).…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Traditional planar slicing requires support structures to print overhangs and complex parts of the object [37]. After the completion of 3D printing process, support structures need to be removed from the main part of the object.…”
Section: Post-printing Phasementioning
confidence: 99%
“…Firstly, the layers’ cohesion is determined by the impregnated material or, alternatively, the fact that the fiber lining the XY plane cannot enhance mechanical strength in the stacking direction. Zhang et al [ 15 , 16 ] observed that the nature of three-dimensional layer-by-layer printing results in the weakest bonding force between the layers. Therefore, in addition to increasing the strength of the CFRTPC filament itself, it is also necessary to study the printing path planning method by laying CFRTPCs to achieve better multiple-direction mechanical reinforcement.…”
Section: Introductionmentioning
confidence: 99%